2002
DOI: 10.1053/ejvs.2002.1617
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Perioperative Haemodynamic Monitoring on Cardiac Morbidity after Major Vascular Surgery in Low Risk Patients. A Randomised Pilot Trial

Abstract: in this study perioperative haemodynamic optimisation was not beneficial.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0
4

Year Published

2005
2005
2014
2014

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(47 citation statements)
references
References 26 publications
0
43
0
4
Order By: Relevance
“…Insertion of PAC is associated with an increased risk of various perioperative complications such as arrhythmia, air embolism, pneumothorax, and pulmonary artery rupture [38]. Also, some studies have suggested that the use of PAC for critically ill patients does not actually improve outcome [39][40][41][42][43][44]. Even with the current risk-to-reward ratio, this device can still occasionally be useful for critically ill patients with low CO undergoing cardiac surgeries and even more rarely in very sick cardiac patients undergoing non-cardiac surgery.…”
Section: Pulmonary Artery Cathetermentioning
confidence: 99%
See 1 more Smart Citation
“…Insertion of PAC is associated with an increased risk of various perioperative complications such as arrhythmia, air embolism, pneumothorax, and pulmonary artery rupture [38]. Also, some studies have suggested that the use of PAC for critically ill patients does not actually improve outcome [39][40][41][42][43][44]. Even with the current risk-to-reward ratio, this device can still occasionally be useful for critically ill patients with low CO undergoing cardiac surgeries and even more rarely in very sick cardiac patients undergoing non-cardiac surgery.…”
Section: Pulmonary Artery Cathetermentioning
confidence: 99%
“…Monitoring of mixed venous oxygen saturation (SvO 2 ) has been used as a simple method for evaluating changes in the systemic oxygen supply to demand ratio in various clinical settings [39,41]. Unfortunately, a PAC is currently required to obtain SvO 2 .…”
Section: Scvomentioning
confidence: 99%
“…Study or Subgroup Bender, 1997Berlauk, 1991Bishop, 1995Boldt, 1998Bonazzi, 2002Boyd, 1993Chytra, 2007Conway, 2002Donati, 2007Fleming, 1992Gan, 2002Kapoor, 2008Lobo, 2000Lobo, 2006Lopes, 2007Mythen, 1995Pearse, 2005Polonen, 2000Sandham, 2003Shoemaker, 1988Shultz, 1985Sinclair, 1997Stone, 2003Takala, 2000Ueno, 1998Valentine, 1997Velmahos, 2000Venn, 2002Wakeling, 2005Wilson, 1999 Ziegler, 1997…”
Section: Resultado: Disfunções Orgânicasmentioning
confidence: 99%
“…Study or Subgroup Bishop, 1995Boldt, 1998Chytra, 2007Fleming, 1992Lobo, 2000Lobo, 2006Lopes, 2007Shoemaker, 1988Shultz, 1985 Total (95% CI) Total events Heterogeneity: Chi² = 3.01, df = 6 (P = 0.81); I² = 0% Test for overall effect: Z = 4.92 (P < 0.00001) Bender, 1997Berlauk, 1991Bishop, 1995Boldt, 1998Bonazzi, 2002Boyd, 1993Fleming, 1992Lobo, 2000Lobo, 2006Polonen, 2000Sandham, 2003Shoemaker, 1988Shultz, 1985Takala, 2000Ueno, 1998Valentine, 1997Velmahos, 2000Wilson, 1999 Ziegler, 1997…”
Section: Resultado: Disfunções Orgânicasmentioning
confidence: 99%
See 1 more Smart Citation